Ensino de biologia e educação ambiental: desenvolvendo estratégias didáticas no Vale do Riacho São José, no agreste do Estado de Pernambuco - Silva, Josefa Eva da (2019)
The São José Valley located in the municipalities of Caetés, Paranatama, Pedra and Venturosa. Agreste de Pernambuco, has as its main vegetation cover the Caatinga biome, with records of paleontological and archaeological goods in its gutter or nearby. In view of the environmental problems that the region is experiencing both regarding climate issues and the interference of large wind energy enterprises in the region, it is necessary to bring the school community closer to this space. The purpose of this paper was to relate the teaching of Biology to Environmental Education with the generating theme of the São José Creek Valley, being the students of the High School of the Reference School in High School (EREM) Luiz Pereira Júnior in the city of Caetés as agents in the construction of this research from an interdisciplinary perspective. Reflection on the relationship between human beings and the environment and the idea of "heritage" was the guiding thread in this study, as anthropic action has been affecting the region. Through teaching and research fieldwork was developed with students, analyzing their perception of the environment in which they are also inserted and a process of self-identification with the place where it is inserted. As motivation for the students' involvement in the proposed activity, a didactic sequence with interdisciplinary activities in a Freirean perspective and a field class was experienced. The performance evaluation was observed with the organization of a photo exhibition, with themes related to the Caatinga biome and the natural and cultural heritage in the school. This study brings the results of the environmental / heritage education work carried out with these students, through which it was possible to demonstrate that it is possible to change perceptions or, at least, to initiate a process of change through education. The final product was a field education environmental education guide for teachers and environmental educators.